1992
DOI: 10.2169/internalmedicine.31.1401
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Cryptococcosis Presenting with Adrenal Insufficiency and Meningitis: Resistant to Prolonged Antifungal Therapy but Responding to Bilateral Adrenalectomy.

Abstract: A case of disseminated cryptococcosis with features of primary adrenal insufficiency and meningitis in an immunocompetent host is presented. Despite antifungal chemotherapy, neither meningitis nor bilateral adrenal gland enlargement was improved. Aspiration biopsy of the adrenal gland revealed necrotic tissue with numerous fungi, suggesting that the adrenal glands were the focus of the persistent fungemia. Removal of bilateral adrenal glands led to improve ment by making the patient more sensitive to antifunga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Cryptococcosis of the central nervous system is life threatening and presents as meningitis or meningoencephalitis, with symptoms such as headache, increased intracranial pressure, fever, lethargy, coma, personality changes, and memory loss [4,9]. Other sites of hematogenous dissemination include skin, bones, joints, kidneys, adrenal gland, spleen, and prostate [7,10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptococcosis of the central nervous system is life threatening and presents as meningitis or meningoencephalitis, with symptoms such as headache, increased intracranial pressure, fever, lethargy, coma, personality changes, and memory loss [4,9]. Other sites of hematogenous dissemination include skin, bones, joints, kidneys, adrenal gland, spleen, and prostate [7,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported disseminated cryptococcosis being refractory to antifungal chemotherapy [6,19]. Serum antigen titers should be obtained in all immunocompetent patients who have cryptococcosis, to monitor the progress of the disease [20].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that (1) prednisolone administered orally was not absorbed enough to suppress the ACTH release due to the protein-losing gastroenteropathy, (2) the patient was in a stressed condition with the disease, and/or (3) he had partial adrenal insufficiency. There are several case reports which have shown the development of adrenal insufficiency in patients with adrenal cryptococcosis, especially when accompanied by meningoencephalitis [5, 6, 11, 13, 21]. It is thus important to follow adrenal function serially in our patient, although he must continue prednisolone therapy for the underlying disease.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to tuberculosis and histoplasmosis, adrenal insufficiency is often improved with resolution of the disease. Adrenal cryptococcal infection resistant to antifungal therapy may respond to adrenalectomy [47]. …”
Section: Other Causes Of Adrenal Infectionsmentioning
confidence: 99%